2019
DOI: 10.1093/ntr/ntz170
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis and Alcohol Co-Use in a Smoking Cessation Pharmacotherapy Trial for Adolescents and Emerging Adults

Abstract: Introduction The co-use of cannabis and alcohol among tobacco-using youth is common. Alcohol co-use is associated with worse tobacco cessation outcomes, but results are mixed regarding the impact of cannabis on tobacco outcomes and if co-use leads to increased use of non-treated substances. This secondary analysis from a youth smoking cessation trial aimed to (1) evaluate the impact of cannabis or alcohol co-use on smoking cessation, (2) examine changes in co-use during the trial, and (3) exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Our results are consistent with trials of treatments for cigarette cessation, the majority of which have found no association between cannabis use and smoking cessation. [27][28][29][30][31][32]35 A recent 21-day diary study of 62 smokers not seeking treatment for cessation also found no association between past year cannabis use and cessation (though their romantic partners' cannabis use was linked to their own cigarette smoking). 39 Other cohort studies of adults have also not observed associations between measures of cannabis use and likelihood of quitting cigarettes after controlling for psychiatric disorders, and alcohol and other drug use disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with trials of treatments for cigarette cessation, the majority of which have found no association between cannabis use and smoking cessation. [27][28][29][30][31][32]35 A recent 21-day diary study of 62 smokers not seeking treatment for cessation also found no association between past year cannabis use and cessation (though their romantic partners' cannabis use was linked to their own cigarette smoking). 39 Other cohort studies of adults have also not observed associations between measures of cannabis use and likelihood of quitting cigarettes after controlling for psychiatric disorders, and alcohol and other drug use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies found no association, [27][28][29][30][31][32] but cannabis use was associated with less cigarette smoking cessation in an Australian study, 33 and in a US study of young adults. 34 A more recent study of youth ages 14-21 35 found no differences in quitting cigarettes at a 26 week follow-up between dual users (of cannabis and cigarettes) vs. nonusers of cannabis; 35 however, during the 12-week varenicline-treatment period, more frequent cannabis use (vs. non-use) was associated with decreased cigarette abstinence. 35 Overall, these clinical studies had relatively small sample sizes, shortterm follow-ups, and by design were limited to smokers who were actively engaged in an organized quit attempt as part of a smoking cessation trial.…”
Section: Cannabis Use and Smoking Cessationmentioning
confidence: 98%
“…Cannabis use predicts tobacco use onset, 61 and co-use is associated with higher toxicant exposure 62 and decreased smoking cessation. 63 Illinois allows tobacco and cannabis to be consumed at the same business location, and no local laws in Illinois prohibiting this activity were found.…”
Section: Discussionmentioning
confidence: 99%
“…33 It seems unlikely that this target will be achieved if cannabis use continues to grow, and coordinated efforts to address tobacco and cannabis use uptake and their co-occurrence among young people should therefore be prioritized to help in achieving this target. Further, co-use of tobacco and cannabis has been shown to lead to poorer smoking cessation outcomes, 34 and while nicotine replacement and behavioural support are well-evidenced cessation aids available to regular youth smokers, 35 youth cessation programmes do not currently address co-use of cannabis; although the feasibility of implementing such an integrated programme has been explored. 36 In the UK, longitudinal evidence shows occasional (early-onset, late-onset) and regular cannabis users have significantly greater odds of nicotine dependence at age 21, compared to non-cannabis users.…”
Section: Discussionmentioning
confidence: 99%